Cyclometallated ruthenium( ii ) complexes with 3-acetyl-2[ H ]-chromene-2-one derived CNS chelating ligand systems: synthesis, X-ray characterization and biological evaluation - Kalaiarasi, G.; Rajkumar, S. Rex Jeya; Dharani, S.; Fronczek, Frank R.; Muthukumar Nadar, M. S. A.; Prabhakaran, R. (New journal of chemistry, 2018)
Four new bivalent organoruthenium complexes incorporated with 3-acetylcoumarin-4( N )-substituted thiosemicarbazones were synthesized. Comprehensive spectral and analytical techniques such as elemental analyses, IR, UV-vis, 1 H NMR and 13 C NMR provided proof of the formation of the complexes ( 1–4 ). Single crystals obtained for two ligands and the four complexes were characterized by X-ray crystallographic studies, which indicated CNS tridentate coordination of the ligands through C–H activation at the C(4) carbon of the pyrone ring of coumarin. The ligands and complexes intercalated with calf thymus DNA (CT DNA), supported by EB displacement studies and DNA viscosity measurements. The compounds bound well with two serum albumins (bovine serum albumin (BSA) and human serum albumin (HSA)) and the quenching mechanism was found to be static. Antioxidant studies revealed the radical scavenging proficiency of the compounds. The compounds showed better antimicrobial activity against two Gram-positive bacteria ( Staphylococcus aureus and Streptococcus pneumonie ), two Gram-negative bacteria ( Pseudomonas aeruginosa and Salmonella paratyphi ) and five fungi ( Candida albicans , Trichophyton rubrum , Aspergillus niger , Aspergillus fumigates and Candida tropicalis ). The in vitro cytotoxic abilities of the compounds were analysed using the MTT assay on MCF-7 (human breast cancer) and A549 (human lung carcinoma) cell lines and compared with standard cisplatin. Activities greater than cisplatin were observed for the ligands as well as the complexes. Assays on the human normal keratinocyte cell line HaCaT showed that the compounds were non-toxic to those cells. In all the biological studies done, the complexes displayed better activity than the ligands and among them, complex 3 stood out as the best, owing to the greater electron donating ability of the N-terminal ethyl group on the thiosemicarbazone. The results implied that N-terminal substitution played a significant role in bringing out the bioactivity of the complexes.